Superalloys 2012 2012
DOI: 10.1002/9781118516430.ch29
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Prior Microstructure Degradation on the High Temperature/Low Stress Non‐Isothermal Creep Behavior of CMSX‐4® Ni‐Based Single Crystal Superalloy

Abstract: The effect of thermal cycling on the creep behavior and life of the second generation Ni-based single crystal superalloy CMSX-4® has been investigated in the very high temperature/low stress domain. Repeated overheatings at 1100°C and/or at 1150°C were introduced in the course of the creep life of the alloy at 1050°C/120 MPa. The detrimental effect of the thermal cycling compared to the isothermal creep behavior of the alloy is shown: thermal cycling leads to an increased average creep strain rate and a reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…As a result, the 9:3 test has the lowest deformation per cycle but the highest strain rate overall, while the 27:3 condition accumulates the most strain per cycle. Similar relationships with varying time at base temperature condition have been published by Raffaitin et al [10] and Giraud et al [4] for thermal cycles to 1150°C.…”
Section: A Test Data From Creep Testsupporting
confidence: 84%
See 1 more Smart Citation
“…As a result, the 9:3 test has the lowest deformation per cycle but the highest strain rate overall, while the 27:3 condition accumulates the most strain per cycle. Similar relationships with varying time at base temperature condition have been published by Raffaitin et al [10] and Giraud et al [4] for thermal cycles to 1150°C.…”
Section: A Test Data From Creep Testsupporting
confidence: 84%
“…The micro-mechanical response under non-isothermal conditions has been shown to reduce the lifetime of an alloy relative to its isothermal creep life. [2,3] By varying the non-isothermal exposure cycles in the temperature range of 1050°C to 1150°C, Giraud et al [4] concluded that one crucial factor for the lifetime reduction is accredited to the development of rafts. This observation is at odds with the well-established beneficial role of c¢-rafting under isothermal conditions.…”
Section: Single-crystal Nickel-based Superalloys Arementioning
confidence: 99%
“…Recent studies have shown that the creep rate under thermal cycling conditions is higher than under isothermal ones and that the lifetime at high temperature is shorter during non-isothermal creep [44,45]. The same last observation was also done by Cormier et al in the case of a single overheating performed after different creep durations under high-temperature/low-stress conditions [46].…”
Section: Introductionmentioning
confidence: 56%
“…Previous research has shown that pre-rafts parallel to the loading direction can enhance TMF properties [36] as well as the non-isothermal creep properties. [21] Another study has shown that rafts parallel to the loading direction may slow down the process of dislocation climb and therefore improve high temperature creep properties. [18] At 1223 K (950°C), the h001i direction is stronger in compression than tension, however the opposite relationship is observed at 1023 K (750°C), where no rafting is visible.…”
Section: B Tension/compression Asymmetrymentioning
confidence: 99%
“…[20] Another study has also shown how N-type of rafts are deleterious to non-isothermal creep properties while rafting of P-type seems to decrease creep rates and therefore enhance the non-isothermal creep properties. [21] The creep performance is strongly influenced by the crystal orientation of the single-crystal superalloy. Literature often concludes that the h011i direction has worse creep properties compared to the h001i and h111i directions.…”
Section: Introductionmentioning
confidence: 99%